Underground coal mine inorganic nanometer reinforcing material and application thereof

By using a reinforced material composed of a variety of inorganic nanomaterials in the coal mine, the problems of poor permeability, low early strength and slow curing speed of existing materials are solved, and the effects of high permeability, high early strength and rapid curing are achieved. , significantly improving the reinforcement effect and coal mining efficiency of underground tunnels of coal mines.

CN119430816APending Publication Date: 2025-02-14SHANXI YUBANG NEW POWER SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411833138.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing underground reinforcement materials in coal mines have problems such as poor permeability, low early strength and slow curing speed, which affects the coal mining efficiency and reinforcement effect.

Method used

Using an inorganic nanoreinforced material for underground coal mines, including components A, components B and components C, through cement, fly ash, gypsum, chain silicate nanomaterials, wetting agents, retarders, graphite oxide The combination of ene/carbon nanotube composite, water glass and water reducer improves the permeability and early strength of the material, and promotes rapid curing of the material through the addition of graphene oxide/carbon nanotube composite and water glass.

Benefits of technology

The material has achieved high permeability, early strength and rapid curing. The compressive strength of 1 day is greater than 15MPa, the compressive strength of 7 days is greater than 70MPa, the flexural strength of 1 day is greater than 5MPa, and the flexural strength of 7 days is greater than 10MPa, which has significantly improved. Reinforcement effect and coal mining efficiency of underground tunnels of coal mines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186421460000081
    Figure BDA0005186421460000081
  • Figure BDA0005186421460000091
    Figure BDA0005186421460000091
  • Figure BDA0005186421460000092
    Figure BDA0005186421460000092
Patent Text Reader

Abstract

The invention provides a coal mine underground inorganic nanometer reinforcing material and application thereof, and belongs to the technical field of reinforcing materials. The coal mine underground inorganic nanometer reinforcing material provided by the invention comprises a component A, a component B and a component C, the mass ratio of the component A to the component B to the component C is 1: (0.1-0.5): (0.8-1.2); the component A comprises 60-90 parts of cement, 20-30 parts of fly ash, 1-5 parts of gypsum, 1-5 parts of a chain silicate nano material, 5-10 parts of a wetting agent and 0.5-2 parts of a retarder; the component B comprises 1-5 parts of a graphene oxide / carbon nanotube compound and 2-5 parts of a surfactant; and the component C comprises 10-30 parts of water glass and 5-10 parts of a water reducing agent. The coal mine underground inorganic nanometer reinforcing material provided by the invention has the characteristics of good permeability, high early strength and rapid curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reinforcement materials, and in particular to an inorganic nano reinforcement material for underground coal mines and application thereof. Background Art

[0002] During the underground coal mining process, under the influence of high ground stress and strong mining, the broken coal mine roadway poses a threat to the safe production of coal mines, and grouting reinforcement is a powerful means to control the broken coal rock in the roadway. Existing underground coal mine reinforcement materials include organic polymer reinforcement materials and inorganic reinforcement materials. However, the common organic polymer reinforcement materials currently include phenolic and polyurea polymer organic reinforcement materials. Such materials are favored by the mine due to their high solidification efficiency and can achieve satisfactory physical strength in a short time, which does not affect the normal mining of coal mines underground, but there are problems such as high cost. The main component of the common inorganic reinforcement material at present is cement. Although it is relatively cheap, the early strength of cement is low, which means that it takes several days to wait for mining after grouting, which affects the efficiency of coal mining; in addition, cement-based inorganic reinforcement materials have the problem of poor permeability and cannot penetrate well into the pores of the broken coal rock mass, which leads to the need for improvement in the reinforcement effect.

[0003] Therefore, there is an urgent need to provide an inorganic nano reinforcement material for underground coal mines with good permeability, high early strength and rapid solidification. Summary of the invention

[0004] The purpose of the present invention is to provide an inorganic nano reinforcement material for underground coal mines with good permeability, high early strength and rapid solidification and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides an inorganic nano reinforcement material for underground coal mines, which comprises a component A, a component B and a component C by weight; the mass ratio of the component A, the component B and the component C is 1: (0.1-0.5): (0.8-1.2);

[0007] The component A comprises: 60-90 parts of cement, 20-30 parts of fly ash, 1-5 parts of gypsum, 1-5 parts of chain silicate nanomaterials, 5-10 parts of wetting agent and 0.5-2 parts of retarder;

[0008] The B component comprises: 1 to 5 parts of a graphene oxide / carbon nanotube composite and 2 to 5 parts of a surfactant; in the graphene oxide / carbon nanotube composite, the graphene oxide is wrapped on the outer surface of the carbon nanotube;

[0009] The C component includes: 10 to 30 parts of water glass and 5 to 10 parts of water reducing agent.

[0010] Preferably, the cement is silicate cement with a strength grade of 42.5.

[0011] Preferably, the particle size of the fly ash is 1 to 100 μm.

[0012] Preferably, the wetting agent includes a polyether wetting agent and / or a polyester wetting agent.

[0013] Preferably, the retarder comprises borax and / or citric acid.

[0014] Preferably, the method for preparing the graphene oxide / carbon nanotube composite comprises: mixing graphene oxide, acidified carbon nanotubes and an organic solvent, and sequentially performing ultrasonic treatment and heat preservation to obtain the graphene oxide / carbon nanotube composite.

[0015] Preferably, the mass ratio of the graphene oxide to the acidified carbon nanotubes is 1:(0.8-1.2).

[0016] Preferably, the insulation temperature is 50-80° C. and the insulation time is 1-2 hours.

[0017] Preferably, the modulus of the water glass is 2.5-3.3.

[0018] The present invention also provides an application of the inorganic nano reinforcement material in coal mines described in the above technical solution, comprising the following steps:

[0019] (1) mixing component A, part of component C and water to obtain a first slurry;

[0020] (2) mixing component B, the remaining component C and water to obtain a second slurry;

[0021] (3) The first slurry and the second slurry are mixed and then injected into the coal rock mass.

[0022] The invention provides an inorganic nano reinforcement material for underground coal mines, which comprises an A component, a B component and a C component by weight; the mass ratio of the A component, the B component and the C component is 1:(0.1-0.5):(0.8-1.2); the A component comprises 60-90 parts of cement, 20-30 parts of fly ash, 1-5 parts of gypsum, 1-5 parts of chain silicate nanomaterials, 5-10 parts of wetting agents and 0.5-2 parts of retarders; the B component comprises 1-5 parts of graphene oxide / carbon nanotube composites and 2-5 parts of surfactants; in the graphene oxide / carbon nanotube composites, graphene oxide is wrapped on the outer surface of carbon nanotubes; the C component comprises 10-30 parts of water glass and 5-10 parts of water reducing agents. The present invention uses cement as the main component of the reinforcement material; the addition of fly ash can improve the permeability of the reinforcement material; gypsum can provide calcium elements, promote the hydration of active components in fly ash, and improve the strength of the reinforcement material; chain silicate nanomaterials can improve the early strength performance of the reinforcement material; wetting agents can improve the permeability of the reinforcement material; retarders can adjust the setting time of the material; graphene oxide / carbon nanotube composites have good dispersibility in the reinforcement material, and at the same time, the addition of one-dimensional materials can improve the density of the reinforcement material, thereby enhancing the compressive strength, flexural strength and toughness of the material; water glass can promote the rapid solidification of the reinforcement material and enhance the structural strength; water reducer can reduce the water consumption and improve the fluidity of the material. The results of the embodiment show that the inorganic nano reinforcement material for coal mines provided by the present invention has low viscosity, good permeability, 1-day compressive strength greater than 15MPa, 7-day compressive strength greater than 70MPa; 1-day flexural strength greater than 5MPa, 7-day flexural strength greater than 10MPa. DETAILED DESCRIPTION

[0023] The present invention provides an inorganic nano reinforcement material for underground coal mines, which comprises a component A, a component B and a component C by weight; the mass ratio of the component A, the component B and the component C is 1: (0.1-0.5): (0.8-1.2), preferably 1: (0.2-0.4): (1-1.2);

[0024] The component A comprises: 60-90 parts of cement, 20-30 parts of fly ash, 1-5 parts of gypsum, 1-5 parts of chain silicate nanomaterials, 5-10 parts of wetting agent and 0.5-2 parts of retarder;

[0025] The B component comprises: 1 to 5 parts of a graphene oxide / carbon nanotube composite and 2 to 5 parts of a surfactant; in the graphene oxide / carbon nanotube composite, the graphene oxide is wrapped on the outer surface of the carbon nanotube;

[0026] The C component includes: 10 to 30 parts of water glass and 5 to 10 parts of water reducing agent.

[0027] In the present invention, unless otherwise specified, the raw materials used in the present invention are all commercially available products in the art.

[0028] The inorganic nano reinforcement material for underground coal mines provided by the present invention comprises component A in parts by weight.

[0029] In the present invention, the A component includes 60 to 90 parts of cement, preferably 65 to 85 parts, and more preferably 70 to 80 parts. In some embodiments of the present invention, the weight of the cement can be 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or 90 parts. In the present invention, the cement is preferably a silicate cement with a strength grade of 42.5. The present invention uses cement as the main component of the reinforcement material, providing the main gelling properties to determine the performance and strength of the reinforcement material.

[0030] Based on 60 to 90 parts by weight of cement, the A component of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 20 to 30 parts of fly ash, preferably 25 to 30 parts. In the present invention, the particle size of the fly ash is preferably 1 to 100 μm, more preferably 10 to 50 μm. The present invention can improve the permeability of the reinforcement material by adding fly ash.

[0031] Based on 60 to 90 parts by weight of cement, the A component of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 1 to 5 parts of gypsum, preferably 2 to 4 parts. In some embodiments of the present invention, the weight of the gypsum can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts. The present invention adds gypsum to provide calcium elements, promote the hydration of active components in fly ash, and improve the strength of the reinforcement material.

[0032] Based on 60 to 90 parts by weight of cement, the A component of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 1 to 5 parts of chain silicate nano materials, preferably 2 to 4 parts. In some embodiments of the present invention, the weight of the chain silicate nano material can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts. In an embodiment of the present invention, the source of the chain silicate nano material can be Lanzhou Nonferrous Construction New Technology Industrial Development Co., Ltd. The present invention adds chain silicate nano materials to improve the early strength performance of the reinforcement material.

[0033] Based on 60 to 90 parts by weight of cement, the A component of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 5 to 10 parts of a wetting agent, preferably 6 to 8 parts. In some embodiments of the present invention, the weight of the wetting agent may be 5, 6, 7 or 8 parts. In the present invention, the wetting agent preferably includes a polyether wetting agent and / or a polyester wetting agent; the polyether wetting agent is preferably a polyether polyol, and the model of the polyether polyol may be PTMEG-1000, PTMEG-2000 or PTMEG-3000. When the present invention uses the above-mentioned polyether polyol, it has a low viscosity, which is more conducive to improving the wettability of each component and improving the permeability of the reinforcement material.

[0034] Based on 60 to 90 parts by weight of cement, the component A of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 0.5 to 2 parts of a retarder, preferably 1 to 1.5 parts. In the present invention, the retarder preferably includes borax and / or citric acid. Adding a retarder in the present invention can adjust the setting time of the material.

[0035] The inorganic nano reinforcement material for underground coal mines provided by the present invention comprises a B component in parts by weight.

[0036] In the present invention, the B component includes 1 to 5 parts of graphene oxide / carbon nanotube composite, preferably 2 to 4 parts. In an embodiment of the present invention, the weight proportion of the graphene oxide / carbon nanotube composite can be 2 parts, 3 parts or 4 parts. In the present invention, the graphene oxide in the graphene oxide / carbon nanotube composite is wrapped on the outer surface of the carbon nanotube. The graphene oxide / carbon nanotube composite used in the present invention has good dispersibility in the reinforcement material. At the same time, the addition of one-dimensional material can improve the density of the reinforcement material, thereby enhancing the compressive strength and flexural strength of the material.

[0037] In the present invention, the method for preparing the graphene oxide / carbon nanotube composite preferably comprises: mixing graphene oxide, acidified carbon nanotubes and an organic solvent, and sequentially performing ultrasonic treatment and heat preservation to obtain the graphene oxide / carbon nanotube composite.

[0038] The present invention has no special limitation on the source of the graphene oxide, and any conventional commercially available graphene oxide or graphene oxide prepared by conventional methods can be used. In the present invention, the graphene oxide is preferably graphene oxide prepared by the Hummers method.

[0039] In the present invention, the method for preparing the acidified carbon nanotubes preferably comprises: mixing the carbon nanotubes with mixed acid, heating and refluxing, and then sequentially washing, ultrasonicating and drying to obtain the acidified carbon nanotubes.

[0040] In the present invention, the carbon nanotubes are preferably single-walled carbon nanotubes; the diameter of the carbon nanotubes is preferably 10 to 20 nm, more preferably 10 to 15 nm, and the length of the carbon nanotubes is preferably 100 to 200 nm, more preferably 150 to 200 nm.

[0041] In the present invention, the mixed acid is preferably a mixed acid of nitric acid and sulfuric acid, the volume ratio of the nitric acid to the sulfuric acid is preferably 1:3; the mass concentration of the nitric acid is preferably 65%, and the mass concentration of the sulfuric acid is preferably 98%. By using the mixed acid, the present invention can acidify the carbon nanotubes and introduce acidic groups such as carboxyl groups on the carbon nanotubes.

[0042] The present invention has no particular limitation on the amount of the carbon nanotubes and the mixed acid, as long as the carbon nanotubes can be completely immersed in the mixed acid.

[0043] In the present invention, the heating reflux temperature is preferably 80-90°C, more preferably 80-85°C; the heating reflux time is preferably 6-10h, more preferably 8-9h. The present invention can acidify the carbon nanotubes by heating reflux, and introduce acidic groups such as carboxyl groups on the carbon nanotubes.

[0044] The present invention does not specifically limit the operation methods of washing, ultrasonication and drying, and conventional washing, ultrasonication and drying operation methods can be used. In the present invention, the washing reagent can be deionized water. The present invention removes the residual mixed acid in the acidified carbon nanotubes by washing. In the present invention, the reagent during the ultrasonication is preferably deionized water, and the power of the ultrasonication is preferably 300-600W, more preferably 500-600W; the ultrasonication time is preferably 30-60min, more preferably 30-40min. The present invention further cuts the carbon nanotubes by ultrasound to improve the assembly ability with graphene oxide. In the present invention, the drying temperature is preferably 80-120°C, more preferably 100-110°C; the drying time is preferably 30-120min, more preferably 60-120min.

[0045] In the present invention, the mass ratio of the graphene oxide to the acidified carbon nanotubes is preferably 1:(0.8-1.2), more preferably 1:(1-1.2). The present invention controls the amount of the two within the above range, which is more conducive to fully wrapping the acidified carbon nanotubes with graphene oxide.

[0046] In the present invention, the organic solvent is preferably N,N-dimethylformamide, N,N-dimethylpropionamide or acetonitrile.

[0047] In the present invention, the ratio of the total mass of the graphene oxide and the acidified carbon nanotubes to the volume of the organic solvent is preferably 1-1.5 mg:1 mL, more preferably 1-1.2 mg:1 mL.

[0048] The present invention has no special limitation on the method for mixing the graphene oxide, the acidified carbon nanotubes and the organic solvent. Conventional methods can be used to uniformly mix the components.

[0049] In the present invention, the power of the ultrasound is preferably 300-600 W, more preferably 500-600 W; the time of the ultrasound is preferably 30-60 min, more preferably 30-40 min. The present invention uses ultrasound to fully unfold the graphene oxide and mix it evenly with the acidified carbon nanotubes.

[0050] In the present invention, the insulation temperature is preferably 50-80°C, more preferably 60-80°C; the insulation time is preferably 1-2h, more preferably 1.5-2h. The present invention can make graphene oxide and acidified carbon nanotubes undergo self-assembly reaction through insulation, so that graphene oxide wraps carbon nanotubes.

[0051] The present invention preferably centrifuges and dries the system obtained by heat preservation to obtain the graphene oxide / carbon nanotube composite. The present invention has no special limitation on the centrifugation and drying methods, and conventional centrifugation and drying methods can be used to fully dry the graphene oxide / carbon nanotube composite.

[0052] Based on the weight of the graphene oxide / carbon nanotube composite being 1 to 5 parts, the B component of the inorganic nano reinforcement material for underground coal mines provided by the present invention comprises 2 to 5 parts of a surfactant, preferably 3 to 4 parts. In the present invention, the surfactant is preferably sodium dodecyl sulfate. The addition of a surfactant in the present invention can improve the stability of the powder in the solution.

[0053] The inorganic nano reinforcement material for underground coal mines provided by the present invention comprises a C component in parts by weight.

[0054] In the present invention, the C component includes 10 to 30 parts of water glass, preferably 15 to 25 parts, and more preferably 20 to 25 parts. In the present invention, the modulus of the water glass is preferably 2.5 to 3.3, and more preferably 3 to 3.3. The addition of water glass in the present invention can promote the rapid solidification of the reinforcement material and enhance the structural strength.

[0055] Based on the weight of water glass being 10 to 30 parts, the C component of the inorganic nano reinforcement material for underground coal mines provided by the present invention includes 5 to 10 parts of water reducer, preferably 6 to 8 parts. In the present invention, the water reducer preferably includes one or more of calcium lignin sulfonate (CLS), modified calcium lignin sulfonate (GCL1-6A), aminosulfonic acid formaldehyde condensate (ASP), naphthalenesulfonic acid formaldehyde condensate (FDN) and sulfonated melamine urea-formaldehyde resin (SMUF), more preferably naphthalenesulfonate formaldehyde condensate high-efficiency water reducer. In the embodiments of the present invention, the source of the naphthalenesulfonate formaldehyde condensate high-efficiency water reducer can be Zhejiang Wulong Admixture Factory. Adding a water reducer in the present invention can reduce water consumption and improve material fluidity.

[0056] The present invention has no special limitation on the preparation method of the inorganic nano reinforcement material for underground coal mines described in the above technical solution. The preparation method of the composition well known to those skilled in the art can be used to evenly mix the components of component A, component B and component C. In an embodiment of the present invention, the mixing device is preferably a dry-mix mortar mixer. The present invention has no special limitation on the parameters of the dry-mix mortar mixer, and can evenly mix the components of component A, component B and component C.

[0057] The present invention also provides an application of the inorganic nano reinforcement material in coal mines, comprising the following steps:

[0058] (1) mixing component A, part of component C and water to obtain a first slurry;

[0059] (2) mixing component B, the remaining component C and water to obtain a second slurry;

[0060] (3) The first slurry and the second slurry are mixed and then injected into the coal rock mass.

[0061] In the present invention, component A, part of component C and water are mixed to obtain a first slurry.

[0062] In the present invention, the portion of component C is preferably one half of the weight of component C.

[0063] In the present invention, the ratio of the total mass of component A and part of component C to the mass of water is preferably 1:0.3-0.5, more preferably 1:0.4-0.5. In the present invention, the ratio of the total mass of component A and part of component C to the mass of water is controlled within the above range, which is more conducive to uniform mixing of component A and part of component C.

[0064] In the present invention, the method for mixing the component A, part of the component C and water is preferably stirring, and the stirring time is preferably 10 to 30 minutes, more preferably 20 to 30 minutes. In an embodiment of the present invention, the stirring device can be a stirrer.

[0065] In the present invention, the B component, the remaining part of the C component and water are mixed to obtain a second slurry.

[0066] In the present invention, the ratio of the total mass of the component B and the remaining component C to the mass of water is preferably 1:0.3-0.5, more preferably 1:0.4-0.5. The present invention controls the ratio of the total mass of the component B and the remaining component C to the mass of water within the above range, which is more conducive to uniform mixing of the component B and the remaining component C.

[0067] In the present invention, the method for mixing the component B, the remaining component C and water is preferably stirring, and the stirring time is preferably 10 to 30 minutes, more preferably 20 to 30 minutes. In an embodiment of the present invention, the stirring device can be a stirrer.

[0068] After obtaining the first slurry and the second slurry, the present invention mixes the first slurry and the second slurry and injects the mixture into the coal rock mass.

[0069] In the present invention, the mixing time of the first slurry and the second slurry is preferably 10 to 30 minutes, more preferably 20 to 30 minutes. In an embodiment of the present invention, the stirring device may be a stirrer.

[0070] In the present invention, the device used for injecting into the coal-rock mass is preferably a grouting pump. The present invention uses a grouting pump to inject the mixed slurry obtained by mixing the first slurry and the second slurry into the coal-rock mass.

[0071] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] The raw materials used in the present invention are:

[0073] Portland cement with strength grade 42.5; fly ash with particle size of 10-50μm; chain silicate nanomaterial (Lanzhou Nonferrous Construction New Technology Industrial Development Co., Ltd.); wetting agent is PTMEG-1000; retarder is borax or citric acid; surfactant is sodium dodecyl sulfate;

[0074] The preparation method of graphene oxide / carbon nanotube composite is as follows:

[0075] Preparation of graphene oxide by Hummers method: P2O5 and K2S2O8 are added to a concentrated sulfuric acid solution under stirring, and after the temperature is raised to 80°C, graphite powder is added, and after the liquid becomes a black viscous substance, the temperature is cooled to 30°C, washed with water and dried to obtain pre-oxidized graphite; concentrated sulfuric acid solution is added to the pre-oxidized graphite under ice-water bath and stirring to obtain a mixed slurry, KMnO4 is added to the mixed slurry, the temperature is raised to 35°C, stirred for 2h, deionized water is added for dilution, and then 30% hydrogen peroxide is added, and the mixture is allowed to stand for 24h, and the lower layer of precipitation is taken for dialysis to obtain graphene oxide; the modulus of water glass is 3; the water reducer is a naphthalenesulfonate formaldehyde condensate high-efficiency water reducer (Zhejiang Wulong Additive Factory);

[0076] The preparation method of acidified carbon nanotubes is as follows: carbon nanotubes with a diameter of 10 to 15 nm and a length of 150 to 200 nm are mixed with a mixed acid (V 65%硝酸 :V 98%硫酸 The mixture was mixed with 1:3), heated under reflux at 85°C for 8h, washed with water until neutral, and then dispersed in water and ultrasonicated at 500W for 30min. The solid obtained by centrifugation was then dried at 100°C for 120min to obtain acidified carbon nanotubes.

[0077] Graphene oxide and acidified carbon nanotubes (mass ratio of 1:1) and N,N-dimethylformamide are ultrasonically treated at 500 W for 30 minutes and kept at 80°C for 1 hour; then centrifuged and dried to obtain a graphene oxide / carbon nanotube composite; wherein the ratio of the total mass of graphene oxide and acidified carbon nanotubes to the volume of N,N-dimethylformamide is 1.5 mg:1 mL.

[0078] Example 1

[0079] An inorganic nano reinforcement material for underground coal mines, which is composed of component A, component B and component C by weight; the mass ratio of component A, component B and component C is 1:0.2:1;

[0080] The component A is composed of 70 parts of cement, 25 parts of fly ash, 2 parts of gypsum, 3 parts of chain silicate nanomaterials, 6 parts of PTMEG-1000 and 1 part of borax;

[0081] The B component is: 3 parts of graphene oxide / carbon nanotube composite and 3 parts of sodium dodecyl sulfate; in the graphene oxide / carbon nanotube composite, graphene oxide is wrapped on the outer surface of the carbon nanotube;

[0082] The C component includes: 20 parts of water glass and 6 parts of water reducing agent;

[0083] The preparation method of the A component is as follows: cement, fly ash, gypsum, chain silicate nanomaterial, PTMEG-1000 and borax are stirred in a dry mortar mixer for 20 minutes to obtain the A component;

[0084] The preparation method of the B component is: stirring the graphene oxide / carbon nanotube composite and sodium dodecyl sulfate in a dry mortar mixer for 5 minutes to obtain the B component;

[0085] The preparation method of the C component is: stirring water glass and a water reducing agent for 5 minutes to obtain the C component.

[0086] Example 2

[0087] The method for using the inorganic nano reinforcement material in coal mines provided in Example 1 is as follows: weigh 100 parts of component A and 60 parts of water, pour them into a mixing tank A, add 50 parts of component C and stir evenly, weigh another 20 parts of component B and 60 parts of water, pour them into a mixing tank B, add 50 parts of component C and stir evenly, connect the mixing tank A and the mixing tank B, stir evenly, and inject into the coal rock mass through a grouting pump.

[0088] The test results of the use effect of the inorganic nano reinforcement material in coal mines of Example 1 are shown in Table 1.

[0089] Table 1 Test results of inorganic nano reinforcement materials in coal mines of Example 1

[0090]

[0091]

[0092] Example 3

[0093] An inorganic nano reinforcement material for underground coal mines, which is composed of component A, component B and component C by weight; the mass ratio of component A, component B and component C is 1:0.5:1;

[0094] The component A is composed of 80 parts of cement, 25 parts of fly ash, 3 parts of gypsum, 3 parts of chain silicate nanomaterials, 8 parts of PTMEG-1000 and 1 part of borax;

[0095] The B component is: 4 parts of graphene oxide / carbon nanotube composite and 5 parts of sodium dodecyl sulfate; in the graphene oxide / carbon nanotube composite, graphene oxide is wrapped on the outer surface of the carbon nanotube;

[0096] The C component includes: 25 parts of water glass and 8 parts of water reducing agent;

[0097] The preparation methods of the A component, the B component and the C component are the same as those in Example 1.

[0098] Example 4

[0099] The method for using the inorganic nano-reinforcement material in coal mines provided in Example 3 is as follows: 100 parts of component A and 60 parts of water are weighed and poured into a mixing tank A, 50 parts of component C are added and stirred evenly, 20 parts of component B and 60 parts of water are weighed and poured into a mixing tank B, 50 parts of component C are added and stirred evenly, the mixing tank A and the mixing tank B are connected, stirred evenly, and injected into the coal rock mass through a grouting pump.

[0100] The test results of the use effect of the inorganic nano reinforcement material in coal mines of Example 3 are shown in Table 2.

[0101] Table 2 Test results of inorganic nano reinforcement materials in coal mines of Example 3

[0102]

[0103]

[0104] Example 5

[0105] An inorganic nano reinforcement material for underground coal mines, which is composed of component A, component B and component C by weight; the mass ratio of component A, component B and component C is 1:0.5:1;

[0106] The component A is composed of 90 parts of cement, 30 parts of fly ash, 4 parts of gypsum, 4 parts of chain silicate nanomaterials, 8 parts of PTMEG-1000 and 1 part of borax;

[0107] The B component is: 5 parts of graphene oxide / carbon nanotube composite and 5 parts of sodium dodecyl sulfate; in the graphene oxide / carbon nanotube composite, graphene oxide is wrapped on the outer surface of the carbon nanotube;

[0108] The C component includes: 30 parts of water glass and 9 parts of water reducing agent;

[0109] The preparation methods of the A component, the B component and the C component are the same as those in Example 1.

[0110] Example 6

[0111] The method for using the inorganic nano-reinforcement material in coal mines provided in Example 5 is as follows: 100 parts of component A and 60 parts of water are weighed and poured into a mixing tank A, 50 parts of component C are added and stirred evenly, 20 parts of component B and 60 parts of water are weighed and poured into a mixing tank B, 50 parts of component C are added and stirred evenly, the mixing tank A and the mixing tank B are connected, stirred evenly, and injected into the coal rock mass through a grouting pump.

[0112] The test results of the use effect of the inorganic nano reinforcement material in coal mines of Example 5 are shown in Table 3.

[0113] Table 3 Test results of inorganic nano reinforcement materials in coal mines of Example 5

[0114]

[0115]

[0116] Comparative Example 1

[0117] An inorganic nano reinforcement material for underground coal mines, which is composed of component A, component B and component C by weight; the mass ratio of component A, component B and component C is 1:0.5:1;

[0118] The component A is composed of 90 parts of cement, 30 parts of fly ash, 4 parts of gypsum, 8 parts of PTMEG-1000 and 1 part of borax;

[0119] The B component is: 5 parts of sodium lauryl sulfate;

[0120] The C component includes: 30 parts of water glass and 9 parts of water reducing agent;

[0121] The preparation methods of the A component, the B component and the C component are the same as those in Example 1.

[0122] The method for using the inorganic nano reinforcement material in a coal mine provided in this comparative example is as follows: 100 parts of component A and 60 parts of water are weighed and poured into a mixing tank A, 50 parts of component C are added and stirred evenly, 20 parts of component B and 60 parts of water are weighed and poured into a mixing tank B, 50 parts of component C are added and stirred evenly, the mixing tank A and the mixing tank B are connected, stirred evenly, and injected into the coal rock mass through a grouting pump.

[0123] The test results of the use effect of the inorganic nano reinforcement material in coal mine underground of Comparative Example 1 are shown in Table 4.

[0124] Table 4 Test results of inorganic nano reinforcement materials in coal mines of comparative example 1

[0125]

[0126] It can be seen from Tables 1 to 4 that the inorganic nano reinforcement material for underground mines provided by the present invention has good permeability, high early strength and fast curing speed, while the inorganic nano reinforcement material for underground mines provided by Comparative Example 1 has lower permeability, early strength and curing speed than the inorganic nano reinforcement material for underground mines provided by the embodiment. This is because the present invention can improve the early strength performance of the reinforcement material by adding chain silicate nanomaterials, and the graphene oxide / carbon nanotube composite can improve the dispersibility of carbon nanotubes, so that it has better dispersibility in the reinforcement material. At the same time, the addition of one-dimensional materials can improve the compactness of the reinforcement material, thereby enhancing the compressive strength and flexural strength of the material.

[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An inorganic nano reinforcement material for underground coal mines, comprising component A, component B and component C by weight; the mass ratio of component A, component B and component C is 1: (0.1-0.5): (0.8-1.2); The A component comprises: 60-90 parts of cement, 20-30 parts of fly ash, 1-5 parts of gypsum, 1-5 parts of chain silicate nanomaterials, 5-10 parts of wetting agent and 0.5-2 parts of retarder; The B component comprises: 1 to 5 parts of a graphene oxide / carbon nanotube composite and 2 to 5 parts of a surfactant; in the graphene oxide / carbon nanotube composite, the graphene oxide is wrapped on the outer surface of the carbon nanotube; The C component includes: 10 to 30 parts of water glass and 5 to 10 parts of water reducing agent.

2. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The cement is silicate cement with a strength grade of 42.

5.

3. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The particle size of the fly ash is 1 to 100 μm.

4. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The wetting agent includes a polyether wetting agent and / or a polyester wetting agent.

5. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The retarder includes borax and / or citric acid.

6. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The preparation method of the graphene oxide / carbon nanotube composite comprises: mixing graphene oxide, acidified carbon nanotubes and an organic solvent, and sequentially performing ultrasonic treatment and heat preservation to obtain the graphene oxide / carbon nanotube composite.

7. The inorganic nano reinforcement material for underground coal mines according to claim 6, characterized in that: The mass ratio of the graphene oxide to the acidified carbon nanotubes is 1:(0.8-1.2).

8. The inorganic nano reinforcement material for underground coal mines according to claim 6, characterized in that: The insulation temperature is 50-80° C. and the insulation time is 1-2 hours.

9. The inorganic nano reinforcement material for underground coal mines according to claim 1, characterized in that: The modulus of the water glass is 2.5 to 3.

3.

10. The use of the inorganic nano reinforcement material for underground coal mines according to any one of claims 1 to 9 comprises the following steps: (1) mixing component A, part of component C and water to obtain a first slurry; (2) mixing component B, the remaining component C and water to obtain a second slurry; (3) The first slurry and the second slurry are mixed and then injected into the coal rock mass.